LEADERSHIP PRACTICES AND TEACHER MOTIVATION IN ISLAMIC VOCATIONAL SCHOOLS: A QUALITATIVE STUDY - Syamsul Kamar; Khamam Khosiin; Benny Prasetya; Muhmammad Alfi Syahrin (Yayasan Adra Karima Hubbi, 2026)
This study examines how school leadership practices affect teacher motivation and professional performance in Islamic vocational education. While leadership has been widely studied in general education, evidence from Islamic vocational schools, especially from the perspective of Islamic Education (PAI) teachers, remains limited. This qualitative case study was conducted in an Islamic vocational school in East Kalimantan, Indonesia, involving the principal and PAI teachers. Data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using thematic analysis. The findings show that visionary, participative, and value-based leadership practices strengthen teachers’ intrinsic motivation, work discipline, professional commitment, and instructional performance. The principal’s ability to integrate institutional goals with Islamic values was found to create a supportive school climate that encourages responsibility and innovation among teachers. The novelty of this study lies in its integrated perspective linking leadership practices, teacher motivation, and professional performance in Islamic vocational education. These results contribute to educational leadership theory and provide practical insights for school leaders seeking to enhance teacher professionalism and learning quality in faith-based vocational schools.